Class I PI 3-kinases: Function and evolution. (September 2015) - Kriplani, Nisha; Hermida, Miguel A.; Brown, Euan R.; Leslie, Nicholas R.
Abstract: In many human cell types, the class I phosphoinositide 3-kinases play key roles in the control of diverse cellular processes including growth, proliferation, survival and polarity. This is achieved through their activation by many cell surface receptors, leading to the synthesis of the phosphoinositide lipid signal, PIP3, which in turn influences the function of numerous direct PIP3 -binding proteins. Here we review PI3K pathway biology and analyse the evolutionary distribution of its components and their functions. The broad phylogenetic distribution of class I PI3Ks in metazoa, amoebozoa and choannoflagellates, implies that these enzymes evolved in single celled organisms and were later co-opted into metazoan intercellular communication. A similar distribution is evident for the AKT and Cytohesin groups of downstream PIP3 -binding proteins, with other effectors and pathway components appearing to evolve later. The genomic and functional phylogeny of regulatory systems such as the PI3K pathway provides a framework to improve our understanding of the mechanisms by which key cellular processes are controlled in humans.